Implentasi Nilai Pendidikan Lelakaq Sasak dalam Pembelajaran Bahasa dan Sastra Indonesia - Mudarman (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
Sasak lelakaq is one of literary works belonging to old poetry, pantun. Sasak lelakaq is built on verse, line, rhyme, sampiran (first two lines of a pantun), and content. This study aimed to describe the implantation of education point of Sasak lelakaq as well as the relevance of Sasak lelakaq’s content and meaning to the Indonesian language and letters teaching. This study was a descriptive qualitative research in the form of “content analysis.” The sampling technique used was purposive sampling on. The data of research was Sasak lelakaq existing in Sakra Timur Sub-district, East Lombok Regency. The data source of research derived from informant. Techniques of collecting data used were interview. The data was analyzed using interactive technique with the procedure including data collection, data reduction, data display, and conclusion drawing. The result of research showed that (1) the meaning of Sasak lelakaq contained religion, social, moral, intellectuality, faith, tough personality, discipline, and responsibility values, and (2) the relevance of Sasak lelakaq’s content and meaning to Indonesian language and letters teaching in line with the objective of national education, to establish the human being who believes in the Almighty God, ethical, civilized, has Indonesian cultural insight, has reasoning, advance, competent, smart, creative, innovative, responsible, has social communication ability, discipline, legally aware, and has health physique thereby becoming an independent human.